2012
DOI: 10.1021/bm300429e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Thermally and Chemically Gelling Injectable Hydrogels for Tissue Engineering

Abstract: Novel, injectable hydrogels were developed that solidify through a dual-gelation, physical and chemical, mechanism upon preparation and elevation of temperature to 37°C. A thermogelling, poly(N-isopropylacrylamide)-based macromer with pendant epoxy rings and a hydrolytically-degradable polyamidoamine-based diamine crosslinker were synthesized, characterized, and combined to produce in situ forming hydrogel constructs. Network formation through the epoxy-amine reaction was shown to be rapid and facile, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 75 publications
(145 citation statements)
references
References 35 publications
(91 reference statements)
3
142
0
Order By: Relevance
“…97 In our research lab, we are able to synthesize magneto-responsive nanocomposite hydrogels by incorporating aminefunctionalized iron (III) oxide nanoparticles into pNiPAAm-based thermogelling macromers with pendant epoxide rings developed by . 63 The key advantage of this technique is that the covalent bonds between the nanoparticles and the scaffold prevent the nanoparticles from leaching out. However, this method is generally less cost-effective than the other methods presented.…”
Section: Synthesis Of Magneto-responsive Biomaterialsmentioning
confidence: 99%
See 4 more Smart Citations
“…97 In our research lab, we are able to synthesize magneto-responsive nanocomposite hydrogels by incorporating aminefunctionalized iron (III) oxide nanoparticles into pNiPAAm-based thermogelling macromers with pendant epoxide rings developed by . 63 The key advantage of this technique is that the covalent bonds between the nanoparticles and the scaffold prevent the nanoparticles from leaching out. However, this method is generally less cost-effective than the other methods presented.…”
Section: Synthesis Of Magneto-responsive Biomaterialsmentioning
confidence: 99%
“…58 Due to PNiPAAm's thermal transition properties, PNiPAAm-based hydrogels have been successfully used as injectable scaffolds because they are able to deliver viable cell populations and can undergo a thermal gelation without having toxic chemical crosslinkers in the injectable hydrogel formulation. 62 However, the challenges that hinder the application of NiPAAm hydrogels from being used as injectable scaffolds are that 63 In their research, they copolymerized PNiPAAm with glycidyl methacrylate (GMA) to form TGMs with pendant epoxy groups which reacted with the amine groups located on the PAMAM, thus forming degradable crosslinks in the hydrogel network. They found that by utilizing PAMAMs as degradable crosslinks they could tune hydrogel swelling/syneresis, degradation time scale and degree of crosslinking ( Fig.…”
Section: Thermo-responsive Biomaterialsmentioning
confidence: 99%
See 3 more Smart Citations